Credential Method as A Measurement Tool for Nurses' Professionalism in A Hospital - Sujiyanti, Sujiyanti; Pratiwi, Arum; Sugiharto, Sugiharto (GLOBAL HEALTH SCIENCE GROUP, 2024)
Credentials as an effort to maintain nurse competency and become the basis for granting clinical authority to nurses have not been implemented well. Implementation of processes for achieving goals varies across institutions. This research aims to identify the relationship between credentialing methods and the outcomes of the Ongoing Professional Practice Evaluation (OPPE) by investigating differences in OPPE scores based on years of experience. This is a quantitative research study with a descriptive correlational and comparative approach, involving 66 respondents who meet the criteria: Nurse PK I; less than 5 years of experience. Data analysis was conducted using Rank Spearman correlation and Kruskal-Wallis tests. The credentialing test method used a portfolio, interview, written test, and practical examination. The research results indicate that 48.48% of credentialing is done using these four methods. The majority of OPPE scores are rated as Good, accounting for 66.67%. The longer a nurse works, the better their performance rating. The Spearman rank test obtained a correlation coefficient of 0.353 with p= 0.004 (p<0.05), and the Kruskal-Wallis test obtained a Kruskal-Wallis value of 41.289 with p=0.000 (p<0.05). Conclusion: There is a relationship between credentialing methods and OPPE scores. The more credentialing methods used, the better the OPPE scores.